BAS/BSCR14 Lipidomic profiling of human atherosclerotic plaques. Issue 17 (26th August 2010) - Stegemann, C; Shalhoub, J; Jenkins, J; Davies, A H; Ladroue, C; Monaco, C; Smith, A; Xu, Q; Mayr, M
Abstract : Rationale: Lipid accumulation in arteries is the hallmark of atherosclerosis. Yet, a comparative lipid analysis of human plaques using state-of-the-art mass spectrometry techniques has not been performed. Methods and results: Comparative lipid profiling of radial arteries and carotid endarterectomies was performed by ultra performance liquid chromatography mass spectrometry. Lipid species were subsequently identified by shotgun lipidomics using a triple quadrupole mass spectrometer. Twenty-two different scan modes in positive and negative ion mode plus additional scans for different fatty acids resulted in the detection of 149 lipid species from nine different classes. Twenty-nine lipid species were only found in endarterectomy specimens. The main qualitative differences between control and diseased arteries were identified among lysophosphatidylcholines, sphingomyelins and cholesteryl esters (CE), including two oxidised CE species. Quantitative mass spectrometric analysis showed that the average concentration of CEs exceeded 30 pmol/μl in atherosclerotic plaques compared with only 0.3 pmol/μl in control arteries. Further analyses focused on plaques from symptomatic and asymptomatic patients and stable and unstable plaque areas from the same lesion. Principal component analysis confirmed that among all the lipids analysed most of the information was in the CEs but no clear discrimination could be obtained between patients (n=24). Conclusions: This study provides the most comprehensive lipid analysis of human atherosclerosis to date. Comparative lipid profiling of control and diseased arteries resulted in the identification of plaque-specific lipids, but failed to unambiguously identify vulnerable lesions.